ANALISIS MODEL MATRIKS PITA (BANDED MATRIX) DALAM MENENTUKAN MAKSIMUM HARGA BIBIT TANAMAN KELAPA SAWIT - -, Istiqomah; Afri, Lusi Eka; -, Hardianto (Universitas Pasir Pengaraian, 2015)
The purpose of this research is to construct banded matrix model and to forming the mathematic model in determining the maximum price of the palm oil seed by usingbanded matrix. One of ways to form it can be down by using a linear system equations that can be arrange to the matrix. The matrix who related with linear system equation can be classified into dense and sparse matrix. The banded matrix is a part of sparse matrix. Based on the results of the tape matrix model on mathematic, the obtained of maximum price on palm oil seeds contained on Rp. 9.000,-